2015
DOI: 10.1186/s12884-015-0697-7
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal adherence to antiretroviral drugs for preventing mother-to-child transmission of HIV in Zambia

Abstract: BackgroundAdherence to antiretroviral (ARV) drugs is essential for eliminating new pediatric infections of human immunodeficiency virus (HIV). Since the Zambian government revised the national guidelines based on option A (i.e., maternal zidovudine and infant ARV prophylaxis) of the World Health Organization’s 2010 guidelines, no studies have assessed adherence to ARVs during pregnancy up to the postpartum period. This study aimed to examine adherence to ARVs and identify the associated risk factors.MethodsA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
41
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 38 publications
9
41
3
Order By: Relevance
“…Similarly, studies have been performed to assess the adherence of pregnant and lactating mothers in Chongwe district, Zambia (82.5%), Nnewi, Nigeria (78.3%), and in a meta-analysis (73.5%) [9,16,19]. Socio-demographic factors may explain the discrepancies with our findings.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Similarly, studies have been performed to assess the adherence of pregnant and lactating mothers in Chongwe district, Zambia (82.5%), Nnewi, Nigeria (78.3%), and in a meta-analysis (73.5%) [9,16,19]. Socio-demographic factors may explain the discrepancies with our findings.…”
Section: Discussioncontrasting
confidence: 82%
“…This finding is supported by studies carried out in Zambia and Malawi [19,20]. The potential reasons could include the poor quality of PMTCT services provided in hospitals due to a large number of PMTCT clients.…”
Section: Discussionsupporting
confidence: 62%
“…This is higher than study reported in Nigeria (80.6%), Zambia (82.5%) and Malawi (72.5%) [8,9,17]. This might be due to good practice of PMTCT and awareness of the participants in the study area and having good regular follow up that increase the adherence rate in the study area.…”
Section: Discussioncontrasting
confidence: 54%
“…Two studies in Ilorin, Nigeria showed that adherence levels in the general HIV-patients population were high: 73.3% 29 A similar study in Zambia reported adherence rates of 82.5% pre-partum 33 . These results that are similar to that of this present study fit into the average of 75.7% adherence rate that was found to be the pre-partum rate in a meta-analysis 34 .…”
Section: Discussionmentioning
confidence: 98%